Analysis of the Use of AI for Learning Malay on the Learning Interest of Phatnawitya Yala School Students - SyubbanulYaum, M. Daffa; Purnamasari, Veryliana; Subekti, V Ervina Eka (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study explores the Use of AI for Malay language learning towards the learning interests of students at Phatnawitya Yala School. The unique context of this school, located in a multicultural area, makes it difficult to create an approach that suits the needs of students. This study uses a quantitative descriptive method to investigate the use of artificial intelligence to study students' learning interests at Phatnawitya Yala School. It is known that the Pre-test score is the score obtained before the implementation of the use of AI in Malay language learning, while the Post-test score is the score obtained after the implementation of the use of AI in Malay language learning. From the scores above, it is known that there is a change of 46.4% that occurs from the range of 0-100% in the use of AI in Malay language learning. This change can be said to be not too big, but it is a positive change, it can be said that the presence of the use of AI in Malay language learning has had a significant impact on improving Malay language learning. The conclusion states that with contextual understanding, teacher engagement, and a focus on student learning outcomes, the use of AI can be an effective tool in improving Malay language learning at the primary level. Continuous evaluation is needed to refine and optimize this implementation, while inclusivity efforts should be strengthened to ensure equitable access and benefits for all students. The implications of this study can provide guidance for other schools looking to integrate AI in language learning in similar contexts.